2006
DOI: 10.1111/j.1365-2788.2006.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of a preventive dental care programme on the prevalence of localized aggressive periodontitis in Down’s syndrome individuals

Abstract: The clinical and radiographic picture found in the present DS group is characteristic of localized aggressive periodontitis. Within the limitations of this study, it seems that the preventive dental programme had no effect on periodontal destruction progression of localized aggressive periodontitis in DS individuals and that impaired oral hygiene plays a relatively minor role in the pathogenesis of this disease. Future controlled studies are needed to assess the effectiveness of different preventive dental pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
(49 reference statements)
5
30
0
Order By: Relevance
“…We have also conducted several community studies (6), but with smaller number of participants or with specialized populations like, for example, Down syndrome (14, 15). In one general study of aging and intellectual disability (10) from the Jerusalem area, we compared persons (40 years and older) living in community residence ( n  = 65) with those living at home ( n  = 43).…”
Section: Dental Care In Israel For This Populationmentioning
confidence: 99%
“…We have also conducted several community studies (6), but with smaller number of participants or with specialized populations like, for example, Down syndrome (14, 15). In one general study of aging and intellectual disability (10) from the Jerusalem area, we compared persons (40 years and older) living in community residence ( n  = 65) with those living at home ( n  = 43).…”
Section: Dental Care In Israel For This Populationmentioning
confidence: 99%
“…In the general population, studies are emerging linking periodontal disease with coronary artery disease (Geerts, Legrand, Charpentier, Albert, & Rompen, 2004). Although data are limited with respect to the rates of periodontal disease among adults with ID, it appears to develop earlier in adults with Down syndrome and is more rapid and extensive than in age‐matched persons from the general population (Zigmond et al., 2006). In spite of similar oral hygiene and gingival measures in a controlled study (Zigmond et al., 2006), persons with Down syndrome had a higher prevalence, extent and severity of periodontitis than the control group.…”
mentioning
confidence: 99%
“…Although data are limited with respect to the rates of periodontal disease among adults with ID, it appears to develop earlier in adults with Down syndrome and is more rapid and extensive than in age‐matched persons from the general population (Zigmond et al., 2006). In spite of similar oral hygiene and gingival measures in a controlled study (Zigmond et al., 2006), persons with Down syndrome had a higher prevalence, extent and severity of periodontitis than the control group. As poor oral care among adults with ID can lead to diseases that may become life threatening, this is an area requiring further investigation.…”
mentioning
confidence: 99%
“…Sakellari et al reported that patients with Down syndrome were unable to perform proper and adequate plaque removal despite good personal and parental levels of cooperation and compliance with frequent visit schedules . Interestingly, Zigmond et al pointed out that a preventive dental program was insufficient to slow the progression of periodontitis in Down syndrome patients . Another study concluded that periodic dental care was not effective in controlling further periodontal disease in special‐care patients with Down syndrome .…”
Section: Discussionmentioning
confidence: 99%